2022
DOI: 10.1002/hep4.2001
|View full text |Cite
|
Sign up to set email alerts
|

Spatial transcriptomics identifies enriched gene expression and cell types in human liver fibrosis

Abstract: Liver fibrosis and cirrhosis have limited therapeutic options and represent a serious unmet patient need. Recent use of single‐cell RNA sequencing (scRNAseq) has identified enriched cell types infiltrating cirrhotic livers but without defining the microanatomical location of these lineages thoroughly. To assess whether fibrotic liver regions specifically harbor enriched cell types, we explored whether whole‐tissue spatial transcriptomics combined with scRNAseq and gene deconvolution analysis could be used to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 32 publications
1
3
0
1
Order By: Relevance
“…The results are also consistent with the low systemic but chronic inflammation observed in Werner syndrome patients [6,39]. More interestingly, increased expression of the immunoglobulin variants IGKC and IGHM has been associated with NAFLD as well as liver fibrosis and cirrhosis in human subjects [40][41][42][43]. Although analyses on the activation status of the immune cells in Wrn Δhel/Δhel mice compared to age-matched wild type mice are required, the measurements of several serum cytokines in the mouse cohorts have indicated an increase of IL-5 in both females and males at ten months of age compared to four months old groups of mice.…”
Section: Discussionsupporting
confidence: 83%
“…The results are also consistent with the low systemic but chronic inflammation observed in Werner syndrome patients [6,39]. More interestingly, increased expression of the immunoglobulin variants IGKC and IGHM has been associated with NAFLD as well as liver fibrosis and cirrhosis in human subjects [40][41][42][43]. Although analyses on the activation status of the immune cells in Wrn Δhel/Δhel mice compared to age-matched wild type mice are required, the measurements of several serum cytokines in the mouse cohorts have indicated an increase of IL-5 in both females and males at ten months of age compared to four months old groups of mice.…”
Section: Discussionsupporting
confidence: 83%
“…Chung et al confirmed that spatial transcriptome analysis by 10× Visium could discriminate well-defined pathological fibrosis areas from parenchymal areas in fresh-frozen human liver tissues from patients with end-stage liver disease. 100 The cell deconvolution analysis by CIBERSORTx 101 detected a significant enrichment of estimated hepatocytes, cholangiocytes, and cycling cells in parenchymal regions and mesenchymal, endothelial, monocyte, innate lymphoid cells, B cells, and T cells in fibrotic areas, consistent with histological assessment. Among the T cell subtypes, T cells expressing CD63 and CD37 (T cells-1) as well as those expressing LTB , KLRB1 , and IL7R (T cells-2) were predominantly localized in the parenchyma, whereas T cells-3/-4 expressing CCL4 and T cells-5 expressing GZMA and CD53 were identified in the fibrotic regions.…”
Section: Spatial Transcriptomics-derived Biological and Clinical Disc...mentioning
confidence: 55%
“…Advanced sequencing techniques have also been used to study pediatric cholestatic liver diseases. Research using single-cell RNA sequencing (Sc-RNA-seq) identified unique tissue-resident T cell populations in human PSC livers (159,160). A new methodology combining Sc-RNAseq with single-nucleus RNA-seq created the first complete transcriptomic map of the human liver (161).…”
Section: Advanced Sequencing and Microscopymentioning
confidence: 99%